2020
DOI: 10.1001/jamasurg.2020.1973
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Recurrence After Liver Resection for Intrahepatic Cholangiocarcinoma

Abstract: IMPORTANCE Although surgery offers the best chance of a potential cure for patients with localized, resectable intrahepatic cholangiocarcinoma (ICC), prognosis of patients remains dismal largely because of a high incidence of recurrence.OBJECTIVE To predict very early recurrence (VER) (ie, recurrence within 6 months after surgery) following resection for ICC in the pre-and postoperative setting. DESIGN, SETTING, AND PARTICIPANTSPatients who underwent curative-intent resection for ICC between May 1990 and July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(140 citation statements)
references
References 42 publications
3
126
0
1
Order By: Relevance
“…Important considerations include the presence of extrahepatic disease; radiologic features such as vascular invasion, multifocality, obvious lymph node involvement, or subtle signs of peritoneal involvement; histopathologic features; degree of Ca 19-9 elevation; response to prior therapies; and genetic and molecular features of the tumor. A large international study of patients who underwent resection of ICC noted that large tumor size, higher number of tumors, microvascular invasion, N1 or NX disease, suspicious/metastatic lymph nodes on preoperative imaging and R1 resection were associated with a higher likelihood of very early recurrence (≤6 months), suggesting some patients may have benefited from neoadjuvant chemotherapy [ 34 ].…”
Section: Indications For Surgerymentioning
confidence: 99%
“…Important considerations include the presence of extrahepatic disease; radiologic features such as vascular invasion, multifocality, obvious lymph node involvement, or subtle signs of peritoneal involvement; histopathologic features; degree of Ca 19-9 elevation; response to prior therapies; and genetic and molecular features of the tumor. A large international study of patients who underwent resection of ICC noted that large tumor size, higher number of tumors, microvascular invasion, N1 or NX disease, suspicious/metastatic lymph nodes on preoperative imaging and R1 resection were associated with a higher likelihood of very early recurrence (≤6 months), suggesting some patients may have benefited from neoadjuvant chemotherapy [ 34 ].…”
Section: Indications For Surgerymentioning
confidence: 99%
“…The high 3-year rate of recurrence that can be up to 80% [4, 5] after curatively intended resection has led to an intensive discussion about the importance of adjuvant therapy concepts. Until 2017, the use of adjuvant treatment was based on meta-analyses from mostly small retrospective phase II studies, which suggested that specifically two high-risk populations benefit from postoperative chemotherapy in terms of mOS: patients with nodal-positive disease and following R1 resection [6, 7].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Adjuvant and/or neoadjuvant therapy concepts may be especially beneficial in patients with a high risk of very early relapse. A recent study showed that very early recurrence within 6 months after surgery occurs in almost 25% of iCCA patients and is associated with a dismal mOS of 13.8 months and a 5-year OS of 8.9%, compared to 59.7 months and 49.8% ( p < 0.001) in patients without very early recurrence [5]. Not surprisingly, tumor size (OR 1.11), number of tumors (OR 1.36), microvascular invasion (OR 1.55), N1 or Nx status (OR 1.94), and R1 resection (OR 2.14) were associated with a higher probability of early recurrence.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…About one fourth of patients develop recurrence within 6 months. In these patients resectability is lower and the results are worse [26]. Tsilimigras et al [26] reported a median survival of 9.3 months and a 5-year-survival of 8.9%.…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…In these patients resectability is lower and the results are worse [26]. Tsilimigras et al [26] reported a median survival of 9.3 months and a 5-year-survival of 8.9%. This poor outcome is a marker for an unfavorable biology of iCCA; thus particular caution should be exercised when indicating surgery.…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%